Tensile Strength of Novel Nonabsorbable PTFE (Teflon®) versus Other Suture Materials: An In Vitro Study - José Arce; Alondra Palacios; Daniel Alvítez-Temoche; G. Mendoza-Azpur; Percy Romero-Tapia; Frank Mayta-Tovalino (Hindawi Limited, 2019)
Objective. To compare the in vitro tensile strength of sutures used in implant surgery according to the type of thread and the immersion time in artificial saliva. Methods. For the development of the study, three suture materials were used: polyglactin 910 (PG), black silk (BS), and Teflon (PTFE) 4-0; 150 samples were used, which were divided among each type of suture and then subdivided into five groups of 10 according to the various immersion times (baseline, 3, 7, 14, and 21 days) in artificial saliva. A universal test machine was used to measure the tensile strength at a speed of 25 cm/min, stretch each sample until the material fails, and record the maximum strength in Newtons (N). Finally, the failure point of the samples was evaluated at 10× increase using a stereromicroscope (Leica Biosystems). Results. When analyzing the tensile strength of the various groups of sutures, it was evidenced that PG maintained its strength, which was lowest at baseline and highest at 21 days. When performing the statistical inference of PG and PTFE, it was found that the force necessary to achieve detachment was not statistically significant (p<0.05). However, it was shown that the force necessary to achieve rupture in the BS group was statistically significant (p=0.001). Conclusion. To sum up, when comparing the in vitro tensile strength of PG, BS, and PTFE sutures at baseline and 3, 7, 14, and 21 days, there was no statistically significant difference. This indicates that all sutures used present sufficient performance that remains resistant as time progresses.